Columbus Day Waltz - Giuseppe Valisi::::::::: (Valisi Bros. & Giorgi)
Piano score, 6 p. On cover: Dedicated to Mrs. Bertha Honore Palmer by kind permision, President of Board of Lady Managers, Worlds Columbian Exposition Lithograph in color of sailing ships with portrait of Columbus flanked by angels symbols of liberty, America and Italy in lower left corner.